2022
DOI: 10.3390/bioengineering9080378
|View full text |Cite
|
Sign up to set email alerts
|

Laser Bioprinting of Cells Using UV and Visible Wavelengths: A Comparative DNA Damage Study

Abstract: Laser-based techniques for printing cells onto different substrates with high precision and resolution present unique opportunities for contributing to a wide range of biomedical applications, including tissue engineering. In this study, laser-induced forward transfer (LIFT) printing was employed to rapidly and accurately deposit patterns of cancer cells in a non-contact manner, using two different wavelengths, 532 and 355 nm. To evaluate the effect of LIFT on the printed cells, their growth and DNA damage pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…The low energy of photons with λ = 1053 nm and the relatively long duration of laser pulses (τ < 7 ns), which do not provide multiphoton absorption, do not lead to the direct destruction of chemical bonds [23]. The studies carried out in [24] showed that even the use of shorter wavelength ultraviolet radiation of 355 nm with a pulse duration of 10 ns (approximately as in our work) leads to negligible genotoxic stress during laser bioprinting. Two optical elements-a telescopic lens with a magnification range of 2×-8× and a motorized beam expander with a magnification range of 1×-3× (Optogama, Vilnius, Lithuania) were used to adjust the beam diameter and change its divergence.…”
Section: Experimental Setup For Bioprinting With Cell Spheroidssupporting
confidence: 54%
“…The low energy of photons with λ = 1053 nm and the relatively long duration of laser pulses (τ < 7 ns), which do not provide multiphoton absorption, do not lead to the direct destruction of chemical bonds [23]. The studies carried out in [24] showed that even the use of shorter wavelength ultraviolet radiation of 355 nm with a pulse duration of 10 ns (approximately as in our work) leads to negligible genotoxic stress during laser bioprinting. Two optical elements-a telescopic lens with a magnification range of 2×-8× and a motorized beam expander with a magnification range of 1×-3× (Optogama, Vilnius, Lithuania) were used to adjust the beam diameter and change its divergence.…”
Section: Experimental Setup For Bioprinting With Cell Spheroidssupporting
confidence: 54%
“…Lastly, stereolithography involves polymerisation of lightsensitive polymers by finely controlled light projected from digital nano-mirrors [29] . It offers low-cost but high quality (resolution of 100 µm), speed, and 90% cell viability [30][31] . It's unlimited by viscosity (1-300 mPa/s) [32] , but its use of ultraviolet light has been shown to damage cell DNA [30][31] .…”
Section: Printing Methodsmentioning
confidence: 99%
“…In addition, it has been extensively shown that LIFT is one of the bioprinting techniques with the highest cell viability, even better than the widely applied extrusion or inkjet printing methods. It guarantees in general the DNA integrity after the transfer process, despite the fact that the cells could suffer some mechanical stresses due to the dynamics of the liquid transfer process, has it has been published in a very recent work even for cancer cell lines [ 63 ] . However, the fact that direct laser irradiation and/or heating of the media containing the cells could affect cell functionality in any extent beyond DNA integrity has been a constant concern in this field, and a number of approaches envisaged the 78 problem of avoiding direct laser irradiation of the cells.…”
Section: Lasers In Ctcs Researchmentioning
confidence: 99%